2023
DOI: 10.3389/fenvs.2023.1059449
|View full text |Cite
|
Sign up to set email alerts
|

Biochar-Soil-Plant interactions: A cross talk for sustainable agriculture under changing climate

Abstract: Biochars provide several agricultural and environmental benefits, such as soil health improvement, better crop growth and yield, carbon sequestration, decreasing greenhouse gas (GHGs) emissions, and regulation of nutrient dynamics. This review highlights the role of biochar in transforming the soil’s physiochemical and biological properties, and their impact on improving seed germination and seedling growth, altering crop physiological attributes, enhancing crop resistance against biotic and abiotic stresses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 342 publications
1
4
1
Order By: Relevance
“…Our results are consistent with these findings; we documented a linear increase in bean germination from 79% in the 0% biochar treatment up to a 100% germination rate in our 26% biochar treatment. These results are inconsistent with the findings of Murtaza et al (2023) that higher rates of biochar application could restrict germination in a variety of plants. We did not identify prior research on the impacts of biochar on the timing of flowering in beans or tomatoes.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are consistent with these findings; we documented a linear increase in bean germination from 79% in the 0% biochar treatment up to a 100% germination rate in our 26% biochar treatment. These results are inconsistent with the findings of Murtaza et al (2023) that higher rates of biochar application could restrict germination in a variety of plants. We did not identify prior research on the impacts of biochar on the timing of flowering in beans or tomatoes.…”
Section: Discussioncontrasting
confidence: 99%
“…This observation is consistent with the review of [ 79 ], who concluded that organic agricultural waste enhances soil health. It is also consistent with the findings of [ 80 ], who found that organic manure was important in plant nutrition in a study in North Western Himalayas, and is also supported by the review of [ 81 ], who observed agronomically beneficial biochar-soil-plant interactions. The manure may also have enhanced soil faunal activities, such as earthworms, improving the structure of soil and cycling of nutrients.…”
Section: Discussionsupporting
confidence: 91%
“…Plant growth is affected by the availability of both micro- and macronutrients in soil in adequate amounts. The availability of micronutrients especially Cu and B perform a remarkable function in plant physiological development and metabolism . Copper is a vital nutrient for plants and actively takes part in many physiological processes which play a significant role in respiration and photosynthesis.…”
Section: Discussionmentioning
confidence: 99%